Diffuse large B-cell lymphoma: sites of extranodal involvement are a stronger prognostic indicator than number of extranodal sites in the rituximab era. Issue 7 (July 2015) - Lu, Chieh-Sheng; Chen, Jia-Hong; Huang, Tzu-Chuan; Wu, Yi-Ying; Chang, Ping-Ying; Dai, Ming-Shen; Chen, Yeu-Chin; Ho, Ching-Liang
Abstract The National Comprehensive Cancer Network (NCCN) International Prognostic Index (IPI) is an enhanced prognostic tool that has identified some specific extranodal sites as a poor prognostic factor. We retrospectively analyzed 148 Taiwanese patients with newly diagnosed diffuse large B-cell lymphoma receiving rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP)-like regimens from January 2001 to December 2010 at the Tri-Service General Hospital. In univarate analysis, ≥ 2 extranodal involved sites had no significant prognostic relevance (p = 0.108), although extranodal involvement of the lung/pleura, liver, lower urinary tract or bone marrow was a statistically significant poor prognostic factor (p < 0.001). In multivariate analysis, specific extranodal sites had a stronger predictive value for poor prognosis (relative risk 3.654, 95% confidence interval 1.514–8.815, p = 0.004) compared with the number of extranodal sites involved. This finding suggests that specific extranodal involved sites have prognostic value in the R era.